1992
DOI: 10.1111/j.1600-0536.1992.tb00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte expressioin of class II MHC antigens in long‐lasting allergic patch test reactions

Abstract: The keratinocyte expression of class II MHC antigens HLA-DR, DP and DQ was studied in 20 long-lasting allergic patch test reactions and 17 normal allergic patch tests reactions. No significant difference in the expression of these antigens in the 2 groups was detected. No 1 allergen was responsible for the majority of long-lasting allergic patch test reactions. The immunological mechanisms which may contribute to long-lasting allergic patch test reactions are discussed with reference to HLA-DR keratinocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
3
8
1
Order By: Relevance
“…The results of this study show LLAPTR occur in 17.9% of the total reactions, a value only slightly higher than that reported by Alderdice et al (4) and by Bygum and Andersen (9), 14.3 and 17% respectively. These results confirm that LLAPTR are a common event if the reactions are checked by means of regular patient recall (2).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The results of this study show LLAPTR occur in 17.9% of the total reactions, a value only slightly higher than that reported by Alderdice et al (4) and by Bygum and Andersen (9), 14.3 and 17% respectively. These results confirm that LLAPTR are a common event if the reactions are checked by means of regular patient recall (2).…”
Section: Discussionsupporting
confidence: 80%
“…In a logistic regression model, Kathon CG sensitivity, atopy and strong patch test positivity proved to be significant risk factors for LLAPTR. The possibility that the same etiological factors behind LLAPTR are inwlved in determining many forms of chronic eczema (2) indicates the need for extensive further research into the subject.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, prevalence of allergy in the general population is unclear because most studies have evaluated populations that had some other immunological sign or symptom. For example, patients who have eczema [41], a history of allergic reaction [49], Ni allergy or allergy to other metals [50,52] or who work in metal refineries [51,53] have been used as cohorts for assessing allergy to Pd ions. A more recent retrospective study used a cohort of dental patients who had received a metallic prosthesis, and found the prevalence of PdCl 2 sensitivity to be 3.8%, based on a patch test [54].…”
Section: Allergy To Pd or Pd Alloysmentioning
confidence: 99%